2022
DOI: 10.1093/bib/bbac377
|View full text |Cite
|
Sign up to set email alerts
|

Self-supervised contrastive learning for integrative single cell RNA-seq data analysis

Abstract: We present a novel self-supervised Contrastive LEArning framework for single-cell ribonucleic acid (RNA)-sequencing (CLEAR) data representation and the downstream analysis. Compared with current methods, CLEAR overcomes the heterogeneity of the experimental data with a specifically designed representation learning task and thus can handle batch effects and dropout events simultaneously. It achieves superior performance on a broad range of fundamental tasks, including clustering, visualization, dropout correcti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…However, our benchmarking of SSL methods revealed the sensitivity to the choice of pre-training strategy. While contrastive methods have shown efficacy in other domains 41,43,44 and specialized in smaller scales in SCG 17,18,[20][21][22][23][24][25][26] , our study found that standard contrastive approaches did not yield as promising results for diverse, large-scale SCG tasks. This result highlights the challenges of applying these methods as generalizable pretext tasks for single-cell data.…”
Section: A Tailored Pre-training Strategy Leads To High Zero-shot Per...mentioning
confidence: 65%
“…However, our benchmarking of SSL methods revealed the sensitivity to the choice of pre-training strategy. While contrastive methods have shown efficacy in other domains 41,43,44 and specialized in smaller scales in SCG 17,18,[20][21][22][23][24][25][26] , our study found that standard contrastive approaches did not yield as promising results for diverse, large-scale SCG tasks. This result highlights the challenges of applying these methods as generalizable pretext tasks for single-cell data.…”
Section: A Tailored Pre-training Strategy Leads To High Zero-shot Per...mentioning
confidence: 65%
“…The cell type labels could refer to biological cell types or the labels of data batches collected from different times or platforms. Following the idea of contrastive learning ( Schroff et al 2015 ; Han et al 2022 ), we employ a contrastive loss in embedding space. It enforces smaller In-Batch distance and larger Between-Batch distance.…”
Section: Methodsmentioning
confidence: 99%
“…During the training phase, after feature selection and term frequency-inverse document frequency (TF-IDF) transformation (see more details in Section 5), we utilize contrastive learning to learn latent representations of the training set, which have yielded state-of-theart results on various tasks in single-cell data analysis [28][29][30]. Specifically, we utilize the multi-layer perceptron (MLP) module within the contrastive learning framework, as suggested by recent studies [31][32][33].…”
Section: The Overview Of Rainbowmentioning
confidence: 99%